Faktor Risiko Kejadian Penyakit Jantung Koroner - Winda Sinthya Naomi; Intje Picauly; Sarci Magdalena Toy (Universitas Nusa Cendana, 2021)
Coronary Heart Disease (CHD) is the leading cause of death in the world for chronic disease. WHO reported 7,4 million people died due to CHD. The highest prevalence of CHD in Indonesia reached 2.650.340 cases of which NTT took the highest number with 137.130 cases. CHD is caused by modified and unmodified factors. Poor dietary patterns such as consuming high amount of carbohydrate, fat, and cholesterol will negatively affect the body and this can be a risk factor for CHD. Education and occupation can also be associated with the health condition. This study aims to analyze the relationship beetween dietary patterns, history of comorbidities, education level and occupation with CHD at Prof W. Z. Yohannes Kupang Hospital in 2020. This research was a case control study. A total sample of 80 was selected that consisted of 40 cases and 40 controls. Data analysis used descriptive and bivariate with chi-square test. Variables associated with CHD were dietary patterns (p=0,029; OR 0,103), history of hypertension (p=0,022; OR 3,316), and history of dyslipidemia (p=0,000; OR 7,909), while history of diabetes mellitus (p=0,094), level of education (p=0,959), and occupation (0,216) were found unrelated with the disease. The efforts to prevent CHD should be improved by controlling the modified factors, managing the dietary patterns and regularly visiting health facilities for health check-up.